Dislocation filter based on LT-GaAs layers for monolithic GaAs/Si integration - Petrushkov, Mikhail O.; Abramkin, Demid S.; Emelyanov, Eugeny A.; Putyato, Mikhail A.; Komkov, Oleg S.; Firsov, Dmitrii D.; Vasev, Andrey V.; Yesin, Michail Yu; Bakarov, Askhat K.; Loshkarev, Ivan D.; Gutakovskii, Anton K.; Atuchin, Victor V.; et al. (Nanomaterials)
The use of low-temperature (LT) GaAs layers as dislocation filters in GaAs/Si heterostructures (HSs) was investigated in this study. The effects of intermediate LT-GaAs layers and of the post-growth and cyclic in situ annealing on the structural properties of GaAs/LT-GaAs/GaAs/Si(001) HSs were studied. It was found that the introduction of LT-GaAs layers, in combination with post- growth cyclic annealing, reduced the threading dislocation density down to 5 × 106 cm−2, the root-mean-square roughness of the GaAs surface down to 1.1 nm, and the concentration of non- radiative recombination centers in the near-surface GaAs/Si regions down to the homoepitaxial GaAs level. Possible reasons for the improvement in the quality of near-surface GaAs layers are discussed. On the one hand, the presence of elastic deformations in the GaAs/LT-GaAs system led to dislocation line bending. On the other hand, gallium vacancies, formed in the LT-GaAs layers, diffused into the overlying GaAs layers and led to an increase in the dislocation glide rate. It was demonstrated that the GaAs/Si HSs obtained with these techniques are suitable for growing high-quality light-emitting HSs with self-assembled quantum dots.